Synergistic Effect of Sodium Oxoalate-Urea on the Flame-Retardancy Imparted to Cotton Fabric - Morteza Mostashari, Seyed; Amirrahmat, Reza; Farkhondeh, Asiay (Asian Journal of Chemistry, 2010)
The synergistic effect between sodium oxalate and urea on the flame-retardancy of cotton fabric (plain construction weighing 168 g/m2) has been of interest in this study. The laundered bonedried weighed samples were impregnated with appropriate concentrations of individual aqueous sodium oxalate or urea solutions and some bunches were impregnated with suitable admixed solutions of both chemicals. An acceptable synergistic effect was experienced using an admixed bath containing 1.0 M equimolar solutions of sodium oxalate and urea for impartation of flame-retardancy to cotton fabric. The optimum add-on value of the mixture expressed in gram anhydrous additive per 100 g fabric was about 17%. The results obtained are in favour of gas theory and also in favour of chemical theory and condensed phase retardation.